2014
DOI: 10.2139/ssrn.2464015
|View full text |Cite
|
Sign up to set email alerts
|

Wine as a Cultural Product: Symbolic Capital and Price Formation in the Wine Field

Abstract: Understanding the valuation of goods in markets has become one of the key topics in economic sociology in recent years. Especially in markets for goods that are valued for their aesthetic qualities, the ascription of value appears to be a complex social process because product quality is highly uncertain. The wine market is an extraordinary example because most consumers and even experts are not able to differentiate between wines based on objective sensory characteristics and cannot rank wines in blind tastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Rengers and Velthuis (2002) look at contemporary art pricing in the Netherlands, focusing on galleries, and taking the art, the artist and gallery parameters as price determinants. In a study of the French wine market, Beckert et al (2016) described wine price formation mechanisms, and as Lehdonvirta did in his study of virtual items, Beckert et al deconstructed wine into several aspects that are believed to play a role in price formation: wine age, year and place of origin, etc. Using a hedonic regression models approach, researchers revealed the relationship between those aspects and the price of wine.…”
Section: Values As Singularities Of Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Rengers and Velthuis (2002) look at contemporary art pricing in the Netherlands, focusing on galleries, and taking the art, the artist and gallery parameters as price determinants. In a study of the French wine market, Beckert et al (2016) described wine price formation mechanisms, and as Lehdonvirta did in his study of virtual items, Beckert et al deconstructed wine into several aspects that are believed to play a role in price formation: wine age, year and place of origin, etc. Using a hedonic regression models approach, researchers revealed the relationship between those aspects and the price of wine.…”
Section: Values As Singularities Of Meaningmentioning
confidence: 99%
“…In the same manner as previous studies (Bowser et al 2015;Livingston et al 2014;Toups et al 2016), this work uncovers the usage and evaluation of items and players' reflections on their experiences of virtual cosmetic goods. It also describes the mechanisms of price formation which have a social nature as they are based mostly on a social and symbolic interpretation of what is good (Lehdonvirta 2009;Lehdonvirta, Wilska, and Johnson 2009;Beckert, Rössel, and Schenk 2016;Beckert and Rössel 2013) and what is not. Moreover, as a previous study has shown, the important role of judgment devices in the evaluation of virtual goods (Musabirov et al 2017), we extend the discussion in this direction by taking price into consideration, answering the following research questions: Methodology, data, and methods…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
“…The wines as well as the vineyard landscape act as trademarks for the whole region (Daniel et al, 2012;Orre-Gordon et al, 2013). Especially the emphasis on wine production as part of the regional tradition can contribute to symbolic positions that are useful for marketing wine or the wine region (Beckert et al, 2014). The United Nations Educational, Scientific and Cultural Organization (UNESCO) has designated multiple vineyard landscapes as World Heritage Sites, including Piedmont Vineyard Landscape in Italy and the terroirs of Burgundy in France (UNESCO, 2016).…”
Section: Cultural Ecosystem Servicesmentioning
confidence: 99%
“…With 5.3% of the Spanish population and 1.4% of the Spanish territory, the Basque Country concentrates 50% of the Spanish "three-starred Michelin restaurants", 5.6% of the "two-starred" ones, and 10.6% of the "one-starred" ones ( Figure 1). As stated by researchers from the Max-Planck-Institut für Gesellschaftsforschung (Cologne), (Beckert, Rössel, and Schenk [27]) "the quality of wine/haute cuisine is determined in a social process that takes place in a field of cultural production. Actors with a high endowment of cultural capital assess wine/haute cuisine quality differently from consumers with low cultural capital.…”
Section: Haute Cuisine: a Cultural Goodmentioning
confidence: 99%
“…Although the production costs of a first image are high, the marginal cost of posterior multiplication of this image border on zero, by virtue of digital technologies (Shapiro and Varian [28]). This facilitates the dissemination of information and provides a series of advantages As stated by researchers from the Max-Planck-Institut für Gesellschaftsforschung (Cologne), (Beckert, Rössel, and Schenk [27]) "the quality of wine/haute cuisine is determined in a social process that takes place in a field of cultural production. Actors with a high endowment of cultural capital assess wine/haute cuisine quality differently from consumers with low cultural capital.…”
Section: Haute Cuisine: a Cultural Goodmentioning
confidence: 99%